عہد ابن سید الناس میں ادب سیرت اور سیرت نگاری کے رجحانات کا جائزہ: A review of Seerah Literature in the Ibn Sayyaid Al-Nas Era and Seerah Biographical Trends - Dr Muhammad Waseem Mukhtar; Saad Jaffar; Dr Nasir Ali Khan (AL- ASAR Islamic Research Journal, 2023)
Presenting the practical manifestation of the Quranic decree, and because of their love and devotion to the Prophet (ﷺ), the Companions adapted their lives to the prophethood. The scholars started presenting the ummah with a practical picture of his life as well as writing it from the beginning. In the 8th century Hijri, the books on the Life of the Prophet (ﷺ) are a part of this series. The books of this century were confiscated and written after being deprived of the knowledge treasure in the Tribulation of Tartar, Due to which their importance increases a lot and It is impossible to avoid them / it is impossible to ignore them. As a result, so many (biographical) books of this century were awarded certificates of acceptance, (Such as Ibn Qayyim’s Zaad al-Ma’ad, Ibn Sayyid al-Nas’ Ayun al-Athar, and Ibn Kathir’s Al-Sirat al-Nabawiyyah, etc.), and also got them primary source status, Which books were written on Seerat Tayyaba during this period? what was their fate? And What style were they representative of? These topics will be highlighted.